Caught in the Middle-Experiences of Student Peer Mentors in Nursing Education: A Qualitative Study - Sara Rivenes Lafontan; Peter Forde Hougaard; Unni Knutstad; Kari Toverud Jensen; Heidi Jerpseth (MDPI AG, 2023)
The use of digital and remote teaching has expanded in higher education and reached a peak during the COVID-19 pandemic. Reducing the social component of the learning process may increase students' isolation, loneliness, and dropout rates. This study aimed to investigate the experiences of student peer mentors who participated in a mentoring program that was implemented to increase student well-being and prevent dropping out among first-year Bachelor of Nursing students at a university in Norway during the COVID-19 pandemic. Eleven semi-structured interviews were carried out with student peer mentors. Using a thematic analysis, four themes were identified: being someone who can ease the transition, defining roles and boundaries, developing communication strategies, and developing their own professional competence. Knowing how difficult the transition to higher education was and being a student during the COVID-19 pandemic made it challenging for the mentors to set boundaries. It was also challenging to develop effective ways to communicate with the first-year students. Being a mentor was considered beneficial for developing professional skills such as empathy and communication and to gain self-confidence. There is a need for more knowledge about how to support mentors in clarifying the peer mentoring role, setting boundaries, and coping with the emotional labor involved in peer mentoring.